2014
DOI: 10.2174/1874226200902010086
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Cigarette Smoke Disrupts CCL20-Mediated Antimicrobial Activity in Respiratory Epithelial Cells

Abstract: Cigarette smoke (CS) exposure is known to increase infection rates, but the mechanisms are not well understood. These studies tested the hypothesis that CS exposure would impair antimicrobial activity of apical conditioned media from human airway (BEAS-2B) cultures by reducing induction and release of the antimicrobial peptide CCL20. BEAS-2B cultures were exposed to CS extract and assayed for temporal and physical characteristics of release as well as for antimicrobial activity. E. coli were exposed to Beas-2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…We have shown that with gas chromatography, it is possible to deliver physiological concentrations of tobacco smoke components to hESCs. Our approach contrasts that of other groups who have exposed cell cultures to tobacco smoke without quantifying the concentration of nicotine or other components that were being delivered (Crane-Godreau et al, 2009; Nana-Sinkam et al, 2007). Although other studies have provided results indicating the potential effects of tobacco components on cells, it is quite possible that those studies introduced toxins at concentrations significantly above physiological levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that with gas chromatography, it is possible to deliver physiological concentrations of tobacco smoke components to hESCs. Our approach contrasts that of other groups who have exposed cell cultures to tobacco smoke without quantifying the concentration of nicotine or other components that were being delivered (Crane-Godreau et al, 2009; Nana-Sinkam et al, 2007). Although other studies have provided results indicating the potential effects of tobacco components on cells, it is quite possible that those studies introduced toxins at concentrations significantly above physiological levels.…”
Section: Discussionmentioning
confidence: 99%
“…In total lung homogenate and induced sputum of patients with COPD, CCL20 protein levels were significantly higher compared with never smokers and smokers without COPD . On the contrary, studies on CSE‐treated human bronchial epithelial cells and primary human nasal epithelial cells showed reduced CCL20 expression and impaired antimicrobial activity in response to CSE. CCL20 shares its antimicrobial activity with the human β‐defensin (HBD)‐2 which interact with the same membrane receptor, CCR6 .…”
Section: Discussionmentioning
confidence: 91%
“…Research in both model systems and human cohorts has suggested that a variety of environmental exposures have consequences for gene expression through epigenetic modes of gene regulation. Particular focus has been placed on four modes of epigenetic regulation, namely DNA methylation, imprinting, histone modifications, and ncRNA-mediated gene regulation (Crane-Godreau et al, 2009). While the study of DNA methylation remains the most widely studied mode of epigenetic regulation, the study of ncRNA-mediated gene regulation has gained significant attention over the past two decades.…”
Section: Epigenetics: Mode By Which Environmental Exposures Influencementioning
confidence: 99%
“…Since partial or imperfect complementarity of a miRNA to a target mRNA can lead to translational repression which can effectively silence a gene, a single miRNA has the capability of regulating a large number of genes (Du and Zamore, 2007). By their mechanisms of negative regulation, miRNA have been shown to exhibit tissue-specific expression and function and play a role in regulating a wide range of biological processes, including differentiation, proliferation, apoptosis, and stress responses (Crane-Godreau et al, 2009). …”
Section: Non-coding Rnamentioning
confidence: 99%
See 1 more Smart Citation